CEUS‐assessed supraspinatus muscle perfusion improves after tendon repair and predicts anatomical and functional outcome: A 1‐year prospective pilot study. Issue 2 (5th May 2022) - Mick, Paul; Kunz, Pierre; Fischer, Christian; Gross, Sascha; Doll, Julian
Abstract: Rotator cuff tear including SSP (Supraspinatus) tendon tears are a very common and often painful condition with several therapeutic options such as tendon repair. Reflected by the high retear rates, the preoperative selection of patients suitable for surgery or conservative treatment, which often yields comparable results, remains difficult. Using contrast‐enhanced ultrasound (CEUS), it is possible to quantify the SSP muscle perfusion as a surrogate parameter for its vitality and healing capabilities. In this study, we enrolled 20 patients who underwent an SSP repair for a preoperative and two postoperative (6 months and 1 year) clinical and sonographic exams including CEUS. Along with functional improvement ( p < 0.001, Constant score), we found a significant increase in CEUS‐assessed muscle perfusion after tendon repair ( p < 0.001). Furthermore, weak preoperative muscle perfusion was associated with a higher risk of a retear ( χ 2 = 0.045) and a moderate trend toward lower postoperative shoulder function that did not reach significance ( r = 0.435; p = 0.055, DASH score). If confirmed in larger studies, CEUS might be a valuable additional diagnostic method for a precise selection of patients who most likely profit from a tendon repair and those who can be treated conservatively with an equally good outcome.